(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Control over the problem of illegal migration as a subsector of migration in the Republic of Latvia is one of the tasks to be implemented by the executive power, such as the Ministry of the Interior and its subordinate institutions, mainly the State Border Guard and the Office of Citizenship and Migration Affairs. The purpose of the article is to study digital technological and legal solutions for controlling illegal migration through the prism of population and national security. The following research methods were used in the development of the study: descriptive, analytical, statistical analysis, inductive method. Results of the study: 1) the regulation of identified digital technological security (tools and means) of illegal migration and problems related thereto, in the context of the position of the State of Latvia in control of illegal migration; 2) the official statistics of illegal migration (data of the State Border Guard of the Ministry of Interior and the Office of Citizenship and Migration Affairs) (statistical data on criminal and administrative offenses) were compiled for the last three-year period, taking into account also latent illegal migration approximate indicators; 3) problems identified in the application of the digital, technical and legal regulation of illegal migration in the State border and within the State, which officials encounter in the practice of law enforcement.